The Effect of Picture Word Inductive Model (PWIM) on Students’ Ability in Writing Descriptive Text at Grade VII of SMP Negeri 1 Pematangsiantar - Lubis, Sri Rahayu; Elseria Silalahi, Dumaris; Saut Raja Sihombing, Partohap (The Future of Education Journal, 2024)
This research aims to investigate the effect of Picture Word Inductive Model (PWIM) strategy to the students’ ability in writing descriptive text. The research design is the quasi-experimental. This research was held at SMP Negeri 1 Pematangsiantar which was conducted in two classes, namely the experimental class (VII-1) consisting of 31 students and the control class (VII-3) consisting of 31 students with the total 62 of 341 students. The writing test is used as the data collection instrument for the pre-test and post-test. The Brown's writing score rubric is used in this research, including several aspects: content, organization, grammar, vocabulary and mechanics. Then the procedure of data analysis in this study was descriptive analysis statistical hypothesis; by finding out the mean score, the median score, and standard deviation is to find out the t-test then examine by t-table. The result of this research, the researcher found out that the results of statistical hypothesis testing is using t-test showed that at the 5% significance (0.05). The t-test was 3,370 while the t-table was 1.670 or t-test > t-table. As a result, H0 is rejected while Ha is accepted. Therefore, it can be concluded that Picture Word Inductive Model (PWIM) strategy significantly affects the students' ability in writing.